Analisis Faktor-Faktor yang Mempengaruhi Disiplin Kerja Guru di MAN 2 Kota Bukittinggi - Asmira, Asmira; Fetri, Yuhana; Asmu’i, Muhammad; Amra, Abhanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Teacher work discipline is one of the important factors in realizing an effective and quality teaching and learning process in schools. This study aims to analyze the factors that affect teacher work discipline in MAN 2 Bukittinggi city. This study uses a qualitative approach with a literature review method. Data collection is carried out through various literature, namely scientific articles sourced from Google Scholar, books, and other documents relevant to the fokus of this research. Data collection was carried out online using the keyword